John Murtagh's general practice - Murtagh, John 1936- (McGraw-Hill Education, 2022)
"Written by renowned general practitioners and educators, and with all content reviewed for currency by leading experts, the eighth edition provides fundamental knowledge and skills required for the challenging field of general practice. Featuring diagnostic strategy models for common presenting problems, including diagnostic triads; Clinical frameworks, including management and treatment; Evidence-based research, with all content reviewed for currency by leading experts; extensive coverage of mental health, health promotion, women's health, and paediatric and geriatric care. New to the eighth edition are chapters on obesity, mood disorders, breast disorders, and traveller's health and tropical medicine. Updated and new information on genetic disorders, chronic pain and infectious diseases, including acute respiratory distress syndrome with reference to coronaviruses and COVID-19." -- Back cover.